Type of primary school attended influences bribe-giving intentions - Mengzhen, Lim; van Oosten, Sanne; Wan Jaafar, Wan Munira (Taylor and Francis, 2024)
This study provides specific insights into bribe-giving intentions in developing societies with diverse populations, using Malaysia as a case study. We investigated whether there are significant variations in young adults’ intentions to offer bribes, depending on the type of primary and secondary schools they attended. We surveyed 345 young adults and tested for significant differences using Mann-Whitney U and Kruskal-Wallis tests. We find that those who attended Chinese vernacular primary schools, as opposed to national primary schools, have a higher intention of giving bribes. We found no significant differences for the type of secondary school attended and bribe-giving intention. The results suggest the need for early anti-corruption education in primary schools in curbing corruption. These insights can aid policymakers and anti-corruption agencies in devising targeted interventions and strategies to diminish bribery. Additionally, they can inform future research concentrating on the socialization environment and the act of giving bribes.